X-Ray Computed Tomography Study of the Microstructure of Superconducting MgB 2 Bulks - Wang, Y; Grovenor, C; Speller, S; Shollock, B; Mousavi, T (Springer, 2025)
MgB2 is a promising candidate for commercial superconducting applications because, as grain boundaries in MgB2 are not weak links, there are fewer limitations on the choice of processing technique compared to high-temperature superconducting (HTS) cuprates. MgB2 bulks are usually manufactured by powder processing techniques followed by a sintering process. After sintering, the impurity phases such as MgO and MgB4 along with porosity are formed which strongly affect the superconducting properties mainly the macroscopic path for supercurrent in MgB2 bulks. Investigation of these microstructural features is essential to improve the superconducting properties of these bulks. In this work, high-resolution laboratory X-ray computed tomography (XCT) has been used to investigate the microstructure of MgB2 bulks in three dimensions. The volume fraction of defects and impurity phases along with the size distribution of pores have been studied using this advanced technique. A comparison has been made between the data extracted from conventional characterization techniques such as XRD and SEM and those obtained from the advanced XCT analysis.